2023
DOI: 10.1371/journal.pone.0290021
|View full text |Cite
|
Sign up to set email alerts
|

Coordinators in the return-to-work process: Mapping their work models

Abstract: Purpose In recent decades, many countries have implemented return-to-work coordinators to combat high rates of sickness absence and insufficient collaboration in the return-to-work process. The coordinators should improve communication and collaboration between stakeholders in the return-to-work process for people on sickness absence. How they perform their daily work remains unexplored, and we know little about to what extent they collaborate and perform other work tasks to support people on sickness absence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Furthermore. it has been shown in other studies as well that they perceive their role differently [ 21 ] and use different work models with regard to whether they select patients and to what extent they choose to collaborate with stakeholders [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore. it has been shown in other studies as well that they perceive their role differently [ 21 ] and use different work models with regard to whether they select patients and to what extent they choose to collaborate with stakeholders [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some reviews have found that RTW coordination has no effect on the RTW rate for people with common mental disorders on sick leave [ 15 , 16 ], others show moderate evidence that RTW coordination results in a higher probability of RTW for a broad spectrum of disorders and injuries [ 17 , 18 , 20 ]. However, the RTWCs’ roles, strategies and responsibilities vary considerably [ 9 , 15 , 21 , 22 ], depending on which sector they are employed in, country-specific legislation, the social insurance system and the healthcare system. In 2020, the Swedish healthcare services became obliged to offer sick-listed patients coordination of the rehabilitation and RTW process if needed.…”
Section: Introductionmentioning
confidence: 99%
“…Many Scandinavian countries, particularly Finland, Norway, Sweden, and Denmark have implemented RTW Coordinators (RTW-C) to enhance communication and collaboration among stakeholders involved in the RTW process [20,21]. Timely RTW is crucial to prevent permanent work disability, and RTW-C provision aims to improve program timing and planning [22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite several literature reviews and metaanalyses of randomised controlled trials, there is ongoing debate about the impact of the RTW-C [22,23]. Some studies suggest that the RTW-C model, or certain components of the model, may reduce the duration of work disability, while others argue that offering RTW coordination has no discernible bene ts compared to usual practice [21,22,24]. Based on the Cochrane review by Vogel et al [23], the uncertainty in evidence regarding the bene ts of RTW coordination programs may be attributed to the low quality of research and variations in the organization and implementation of these programs.…”
Section: Introductionmentioning
confidence: 99%
“…In another study based on longitudinal data, employees with reduced work ability who received support from RCs (employed by the employer) were found to have a higher risk of sickness absence but a lower risk of later disability retirement compared to employees who did not receive such support [ 30 ]. Although the overall role of RCs is to facilitate individuals’ RTW and support communication and cooperation among different actors involved in the rehabilitation process [ 29 , 31 ], the working methods and efforts used may vary [ 32 ]. It is, therefore, unclear whether the coordinators involved in the RTW process, as described in the international research (often called RTW coordinators), usually placed in companies or insurance agencies, correspond to the RC function that exists in Swedish healthcare.…”
Section: Introductionmentioning
confidence: 99%